TEACHER PROFESSIONAL COMPETENCE AND ITS INFLUENCE ON STUDENT LEARNING MOTIVATION: INSIGHTS FROM SMAN WELULI - Heribertus Dasi; Yonly A. Benufinit; Jhon Enstein (Universitas Citra Bangsa, 2024)
This study aims to determine and measure the effect of teacher professional competence on student learning motivation at SMAN Weluli. Quantitative method together with associative research design was employed, data werely gathered via questionnaires from 20 students and 10 teachers. The results of the analysis revealed that there was a significant but weak connection between teacher professional competence with student learning motivation with determination coefficient equal to 4.5%. Simple regression tests showed that teacher competence contributed 4.5% to the variability of student learning motivation, while the other 95.5% was influenced by other factors. This study confirms the importance of improving teacher professional competence, especially in the pedagogical aspect, to support student learning motivation. On the other hand, these research results reveal a more holistic approach to enhancing motivation for student learning should be through exploring various other external factors. This study suggests that, further studies may be conducted using larger and more various samples with regard to variables such as family support and learning facilities to provide a more comprehensive understanding.